Development of 3N-Oriented TPACK Mathematical Computing E-Modules - Kuncoro, Krida Singgih; Arigiyati, Tri Astuti (Universitas PGRI Madiun, 2020)
Technology always develops from time to time and is very closely related to real-life, which is to solve everyday problems. This study aims to describe the design of 3N-oriented TPACK-based mathematical computing modules (niteni, nirokke, nambahi). The method used is descriptive qualitative part of development research. This research resulted in an E-module design. Mathematical Computing E-Module has the following characteristics (1) containing the TPACK concept and 3N teachings that are designed to be attractive, (2) showing the appropriate 3N activities in the lecture process, and (3) inviting students to carry out niteni, nirokke, and nambahi activities during lesson. The design of 3N-Oriented TPACK based on Mathematical Computing E-Modules is declared valid.